2022
DOI: 10.1159/000523713
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Kidney Outcomes of Anti-Glomerular Basement Membrane Disease in a Large Chinese Cohort

Abstract: <b><i>Introduction:</i></b> Anti-glomerular basement membrane (GBM) disease is a rare but the most aggressive form of glomerulonephritis. To dissect the prognostic factors, we retrospectively analyzed the clinical features of a large cohort and compared the clinical features and prognosis during decades. <b><i>Methods:</i></b> Data on clinical manifestation, treatment, and prognosis were collected. Cox models and receiver operating characteristic (ROC) curve were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Several clinical indicators have been demonstrated to be independently associated with kidney survival, including the levels of anti-GBM antibodies, kidney function, oligoanuria, and dialysis at presentation in previous studies. 6 , 8 Likewise, histological parameters have been studied, highlighting the importance of the proportion of normal glomeruli and crescents. 6 , 7 , 8 In the present cohort, we found that the percentage of normal glomeruli at the time of kidney biopsy and initial need for RRT comprised the 2 strongest independent predictors for kidney outcomes, which was in line with the original publication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several clinical indicators have been demonstrated to be independently associated with kidney survival, including the levels of anti-GBM antibodies, kidney function, oligoanuria, and dialysis at presentation in previous studies. 6 , 8 Likewise, histological parameters have been studied, highlighting the importance of the proportion of normal glomeruli and crescents. 6 , 7 , 8 In the present cohort, we found that the percentage of normal glomeruli at the time of kidney biopsy and initial need for RRT comprised the 2 strongest independent predictors for kidney outcomes, which was in line with the original publication.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Approximately 60% to 80% patients entered ESKD with maintenance RRT within the first year of follow-up. 2 , 3 , 4 , 5 , 6 , 7 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…10,14,18 Importantly, some studies have suggested that patients with both ANCA and anti-GBM antibodies may be at higher risk of severe disease, and similar to the patient described here, this "double-positivity" may contribute to worse outcomes. [19][20][21] Nonetheless, we believe one consideration that warrants revisiting is the recommended frequency of TPE.…”
Section: Discussionmentioning
confidence: 99%